Multiple antibiotic resistance and virulence factors of Staphylococcus aureus strains isolated from dairy farms in South Sulawesi, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Juwita S, Indrawati A, Damajanti R, Safika, Mayasari NLPI. 2021. Multiple antibiotic resistance and virulence factors of Staphylococcus aureus strains isolated from dairy farms in South Sulawesi, Indonesia. Biodiversitas 23: 1015-1022. Antimicrobial resistance (AMR) is an important issue affecting human and animal health worldwide. This study aimed to investigate antibiotic resistance and determine the virulence factors of S. aureus isolated from the dairy farms in South Sulawesi, Indonesia. Thirty-one isolates of S. aureus were tested for sensitivity to 9 types of antibiotics using the Kirby-Bauer disk diffusion method. The analysis of antibiotic resistance and virulence genes in S. aureus isolates was performed by the conventional PCR method. The results showed that S. aureus isolates from human samples were resistant to penicillin G (PEN) (86%), ampicillin (AMP) (86%), oxacillin (OXA) (14%), cefoxitin (FOX) (14%), tetracycline (TET) (43%) and ciprofloxacin (CIP) (14%). Staphylococcus aureus isolates from the animal samples were resistant to penicillin G (PEN) (50%), ampicillin (AMP) (50%), tetracycline (TET) (15%), and erythromycin (5%). Meanwhile, S. aureus isolates from dangke were resistant to penicillin G (PEN) and ampicillin (AMP) (50% each). Antimicrobial resistance genes for blaTEM (83%), mecA (17%), and tetA (100%) were detected in S. aureus isolates from human samples, whereas those for blaTEM (90%) and tetA (100%) were detected in isolates from animal samples. Meanwhile, the genes for blaTEM (100%) were detected in isolates from dangke. A total of 19 S. aureus isolates harbored the virulence gene for fnbA (26%), clfA (58%), hla (58%), and tst (21%). The use of antibiotics in humans and animals needs to be implemented properly in local communities to prevent the spread of antibiotic resistance. The presence of the tst gene in raw milk is essential for consumer protection against the risk of toxic shock syndrome.
Keywords: Antibiotic resistance genes, dairy farm, one health, Staphylococcus aureus, virulence factor gene